1995
DOI: 10.1007/bf00210403
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of phenotypic variation in patients with argininemia

Abstract: Argininemia is an autosomal recessive disorder caused by a deficiency in the liver-type arginase enzyme. Clinical manifestations include progressive spastic diplegia and mental retardation. While the quality of life can severely deteriorate in most such patients, some do show remarkable improvement in neurological symptoms while on controlled diets. We examined the thesis that differences in clinical responses to dietary treatment are based on molecular heterogeneity in mutant arginase alleles. Genomic DNAs fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 19 publications
0
43
0
Order By: Relevance
“…Nonsense mutations have been reported in a minority of patients, with missense mutations being more prevalent [Uchino et al, 1995;Vockley et al, 1994]. Many of these missense mutations occur in highly conserved regions of the gene .…”
Section: Molecular Characteristicsmentioning
confidence: 99%
“…Nonsense mutations have been reported in a minority of patients, with missense mutations being more prevalent [Uchino et al, 1995;Vockley et al, 1994]. Many of these missense mutations occur in highly conserved regions of the gene .…”
Section: Molecular Characteristicsmentioning
confidence: 99%
“…Hyperargininemia is a heterogeneous disease resulting from point mutations throughout the type I arginase gene (11)(12)(13)(14)(15)(16)(17). An R291X mutation has been identified that would lead to the production of a truncated protein lacking the final 32 amino acids at the C terminus of the 323 amino acid subunit.…”
mentioning
confidence: 99%
“…At least 12 distinct disease-causing mutations in ARG1 have been identified so far in different human populations, indicating that argininemia is heterogeneous at the molecular level (Haraguchi et al, 1990;Grody et al 1992;Uchino et al 1992, Vockley et al, 1994Uchino et al, 1995). In this work we extend the sequence data on arginase deficiency by characterizing a novel R21X mutation found in four homozygous Portuguese patients with argininemia.…”
Section: Introductionmentioning
confidence: 60%
“…Based on the results from in vitro expression tests, Uchino et al (1995) proposed that ARG1 pathogenic mutations could be classified as either severe or moderate and further suggested that the clinical responses to dietary treatment were correlated with the nature of these mutations. Among the severe mutations, Uchino et al (1995) included the deletion 77delA, which leads to a shift in the reading frame after aminoacid residue 26 and creates a premature termination at codon 31.…”
Section: Arg1 R21x Substitution and Argininemia 5 Discussionmentioning
confidence: 99%
See 1 more Smart Citation